Analisis Karakteristik Ekonomi Desa di Wilayah Daratan Provinsi Riau Menurut Indeks Desa Membangun (IDM) Tahun 2022 - Nisa, Novriza Awwalin; Rifai, Ahmad; Kurnia, Deby (Universitas Galuh, 2024)
Village development according to the village development index (IDM) in 2022 in Riau province experienced changes in developed and independent villages which increased while very underdeveloped and underdeveloped villages decreased. However, Riau province's IDM ranking is still in developing status with a value of 0.7012. The IKS value is 0.7861, the IKE value is 0.5979 and the IKL value is 0.7195. Of the three composite indices, the economic resilience index (IKE) has the lowest value compared to the social resilience index (IKS) and environmental resilience index (IKL). This study aims to identify and analyze the economic characteristics of villages based on the level of village development status according to IDM in 2022 in the mainland area of Riau province. This research uses quantitative descriptive method with kruskal-wallis analysis. The results showed that there were significant differences in village economic characteristics at all levels of village development status according to the Village Development Index (IDM) in 2022, seen from the Asymp. Sig. or p value is 0.000 which is <0.05. Village superior products in developing villages are more diverse compared to other village statuses, with an average of rice and palm oil commodities. Micro and small industries in independent villages are more numerous compared to other village statuses, with an average of 70 industries consisting of household industries, tourism, fisheries, agriculture, livestock and other industries. The availability of shops in independent villages is more than in other village statuses, with an average of 111 shops. Market access in independent villages is more feasible and conducive than in other village statuses, with an average market with permanent buildings. Access to financial/banking institutions in independent villages is more diverse compared to other village statuses, with an average of BUMDes and government banks. The status of BUMDes in independent villages is, on average, active compared to other village statuses. The turnover of BUMDes in independent villages is larger compared to other village statuses, with an average of IDR 478,011,655. BUMDes business sectors in independent villages are more numerous compared to other village statuses, with an average of 6 sectors consisting of services, savings and loans, agriculture, BRIlink, groceries and business groups. Village own-source revenues in independent villages are higher compared to other village statuses, with an average of IDR 108,456,305. Village funds in developed villages are more than other village statuses, with an average of 3,643,684,268 rupiah.